An assessment of voluntary debt review termination and the shortcomings of the National Credit Act in relieving the debt burden of over-indebted consumers in South Africa - Brown, Robin-Lee (University of the Witwatersrand, Johannesburg, 2023)
Among other objectives, two of the primary goals of the National Credit Act (NCA) are to help over-indebted consumers and to prevent the abuse of credit. This research report examines the NCA’s legal framework and impact of the NCA on over-indebted consumers with regard to debt review and the voluntary termination process. This research report delves into the challenges that consumers face when attempting to voluntarily terminate debt review prior to their debts being paid off in full as seen in the Van Vuuren case whereby a consumer was unable to exit debt review despite having the means to manage his own finances. The conclusion reached in this study is that, while the NCA has introduced a procedure which results in the reduction of over-indebtedness among consumers, there are issues with the debt review regime that should be addressed. The report further concludes with recommendations for improving the NCA’s debt review regime and providing an enhanced debt relief procedure for consumers in the Republic of South Africa. By adopting these recommendations, the debt review process will further advance the interests and protection of consumers
A research report submitted in partial fulfilment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2023
Keywords: National Credit Act; Over-indebtednes; Debt review; Voluntary termination; Dignity; Just administrative access; Access to courts; Recommendations; Comparative analysis; UCTD; SDG-8: Decent work and economic growth